The Effect of Pre‐Appointment Consultation Triage on Patient Selection and Revenue Generation in a University Rheumatology Practice. Issue 5 (25th April 2019) - West, Sterling G.; Pearson, Duane W.; Striebich, Christopher C.; Goecker, Ryan; Kolfenbach, Jason R.
Abstract : Objective: To evaluate the effectiveness of pre‐appointment consult screening to identify patients with autoimmune and inflammatory rheumatic disease (AIRD) and to evaluate the revenue implications of routine outpatient care of patients with AIRD compared to that of non‐AIRD patients. Methods: Using data in the electronic medical records, we retrospectively analyzed all new outpatients who were referred for rheumatology consults during a 9‐month period for a final diagnosis and revenue generation for routine outpatient care over 1 year following the consult review or initial evaluation. Results: A total of 961 patients were referred to the outpatient rheumatology clinic and underwent pre‐appointment triage. Overall, 673 patients were approved for evaluation of AIRD, and 288 patients were denied rheumatology consultation. Patients were seen an average of 13 days after the consult review. Among patients who were approved for consult, 597 came for evaluation, with 357 diagnosed as having an AIRD and 240 with a non‐AIRD. Among patients who were denied a consult, 128 had 1‐year follow‐up data, with 6 patients eventually diagnosed as having an AIRD (consult triage sensitivity 98%, positive predictive value 60%). The consult triage system allowed more AIRD patients to be seen over a 1‐year period. Revenue data for outpatient care was available for 318 of 357 patients with an AIRD and 192 of 240 non‐AIRD patients and showed that care for patients with an AIRD generates 44 times more revenue compared to care for non‐AIRD patients (5, 877 per AIRD patient versus 134 per non‐AIRD patient; P < 0.001). Conclusion: Pre‐appointment consult screening is an effective method to identify patients with an AIRD. This approach enables timely access to care for patients with the highest need for evaluation and results in significantly more revenue generation.